Fatal Fulminant Epstein–Barr Virus (EBV) Encephalitis in Immunocompetent 5.5-Year-Old Girl—A Case Report with the Review of Diagnostic and Management Dilemmas - Magdalena Mierzewska-Schmidt; Anna Piwowarczyk; Krystyna Szymanska; Michal Ciaston; Edyta Podsiadly; Maciej Przybylski; Izabela Pagowska-Klimek (Biomedicines)
Introduction: Epstein–Barr virus (EBV) usually causes mild, self-limiting, or asymptomatic infection in children, typically infectious mononucleosis. The severe course is more common in immunocompromised patients. Neurological complications of primary infection, reactivation of the latent infection, or immune-mediated are well-documented. However, few published cases of fatal EBV encephalitis exist. Case presentation We report a case of a 5.5-year-old immunocompetent girl with fulminant EBV encephalitis fulfilling the criteria for the recently proposed subtype Acute Fulminant Cerebral Edema: (AFCE). The child presented with fever, vomiting, altered mental status, and ataxia. Her initial brain CT (computed tomography) scan was normal. On day 2 she developed refractory status epilepticus requiring intubation, ventilation, and sedation for airway protection and seizure control. Magnetic resonance imaging (MRI) scan showed cytotoxic brain edema. Despite intensive treatment, including acyclovir, ceftriaxone, hyperosmotic therapy (3% NaCl), intravenous immunoglobulins (IVIG), corticosteroids, as well as supportive management, on day 5 she developed signs of impending herniation. Intensification of therapy (hyperventilation, deepening sedation, mannitol) was ineffective, and a CT scan demonstrated generalized brain edema with tonsillar herniation. EBV primary infection was confirmed by serology and qPCR in blood samples and post-mortem brain tissue. An autopsy was consistent with the early phase of viral encephalitis. Conclusions This case confirms that normal or non-specific CT and MRI scans do not exclude encephalitis diagnosis if clinical presentation fulfills the diagnostic criteria. The implementation of prophylactic anticonvulsants could improve outcomes. Intracranial pressure (ICP) monitoring should be considered in AFCE for better ICP management. Decompressive craniectomy might be a life-saving option in refractory cases. An encephalitis management algorithm is proposed.